Leveraging artificial intelligence to meet the sustainable development goals - Ziemba Ewa Wanda; Duong Cong Doanh; Ejdys Joanna; Gonzalez-Perez Maria Alejandra; Kazlauskaitė Ruta; Korzynski Pawel; Mazurek Grzegorz; Paliszkiewicz Joanna; Stankevičienė Jelena; Wach Krzysztof (Journal of Economics and Management)
Aim/purpose – This study aims to identify the role of Artificial Intelligence (AI) in achieving the Sustainable Development Goals (SDGs), with specific reference to their targets, and to present good practices in this regard.